Factors Affecting Financial Reporting for Decision Making Among Selected Small and Medium Enterprises in the Oil and Gas Sector in Malaysia - Teoh, Say Hean (2023)
Financial reporting for decision-making is crucial as it demonstrates the organisation study of costs, expenditures, and cash flow. Given the prevalence of sustainability and external reporting, it has been expected that financial reporting gains significance among O&G SMEs. While earlier research observed the impact between management characteristics, particularly human capital attributes, and financial reporting responsiveness, the studies on the link between management characteristics and financial reporting responsiveness have been limited. Moreover, given the importance that managers place on the financial reporting process, specifically after the adoption of financial activities on managerial skill and financial reporting timeliness, evidence regarding the factors affecting financial reporting for decision-making purposes among Malaysian O&G SMEs is lacking. Therefore, this study aims to investigate the factors affecting financial reporting for decision-making in O&G SMEs. A complete analysis of the literature indicates a significant correlation between the qualification of accounting staff, managers’ skills, preparation of financial statements, comprehensive financial information, and financial literacy in the financial reporting decision-making among O&G SMEs. This study data was collected through an online survey (Google Forms) of 152 O&G SMEs across Malaysia and Statistical Package for the Social Sciences (SPSS) version 25. The SPSS was also used to test the study hypotheses via multiple regression analysis. As a result, it was found that the accounting staff's qualifications, the managers’ skills, the preparation of financial statements, the availability of comprehensive financial information, and financial literacy directly affected the financial reporting decisions by O&G SMEs. Additionally, the findings demonstrated that the O&G SMEs adopted an optimal level of financial reporting decision-making, with the optimisation of comprehensive financial information, manager skill, and financial literacy as the top priorities. The literature, policy, and management contributions, limitations, and future research suggestions are highlighted.